14‐3‐3ζ binds to and stabilizes phospho‐beclin 1S295 and induces autophagy in hepatocellular carcinoma cells. Issue 1 (11th November 2019) - Tang, Yufu; Zhang, Yibing; Liu, Shupeng; Sun, Zhongyi; Wang, Chunhui; Li, Longfei; Zhou, Wenping; Cheng, Shuqun
Abstract: Data from The Cancer Genome Atlas (TCGA) indicate that the expression levels of 14‐3‐3ζ and beclin 1 (a key molecule involved in cellular autophagy) are up‐regulated and positively correlated with each other ( R  = .5, P  < .05) in HCC tissues. Chemoresistance developed in hepatoma cancer cells is associated with autophagy initiation. This study aimed to explore 14‐3‐3ζ's role in regulating autophagy in HCC cells, with a focus on beclin 1. The co‐localization of 14‐3‐3ζ and beclin 1 was detectable in primary HCC tissues. To simulate in vivo tumour microenvironment (hypoxia), CSQT‐2 and HCC‐LM3 cells were exposed to 2% oxygen for 24 hours. The protein levels of 14‐3‐3ζ and phospho‐beclin 1 S295 peaked at 12 hours following hypoxia. Meanwhile, the strongest autophagy flux occurred: LC3II was increased, and p62 was decreased significantly. By sequencing the coding area of BECN 1 gene of CSQT‐2 and HCC‐LM3 cells, we found that the predicted translational products of BECN 1 gene contained RLPS 295 VP (R, arginine; L, leucine; P, proline; S, serine; V, valine), a classic 14‐3‐3ζ binding motif. CO‐IP results confirmed that 14‐3‐3ζ bound to beclin 1, and this connection was markedly weakened when S 295 was mutated into A 295 (alanine). Further, 14‐3‐3ζ overexpression prevented phospho‐beclin 1 S295 from degradation and enhanced its binding to VPS34, whilst its knockdown accelerated the degradation. Additionally, 14‐3‐3ζ enhanced the chemoresistance of HCC cells to cis‐diammined dichloridoplatium by activating autophagy. Our work reveals that 14‐3‐3ζ binds to and stabilizes phospho‐beclin 1 S295 and induces autophagy in HCC cells to resist chemotherapy.